Total antioxidant status at high altitude in lowlanders and native highlanders: Role of uric acid - Sinha, S.; Singh, S. N.; Ray, U. S. (High Altitude Medicine & Biology, 2009)
Hypobaric hypoxia causes oxidative stress and the antioxidant system of the body plays a vital role in controlling it. Urate contributes up to two-thirds of the antioxidant capacity of human blood. The urate production is catalyzed by xanthine oxidase with a concomitant release of free radicals. This study was designed to appraise the role of urate as an antioxidant at high altitude. The study was conducted on 92 male lowlanders and 66 highlanders after ascent to high altitude at 4560m. Blood was collected at sea level and after 4 weeks of high altitude exposure. In lowlanders, a significant increase in levels of hydroperoxide (551.4±4.2µmol/mL vs. 582.0±3.55, p<0.001], protein carbonyl (2.4±0.11µmol/mL/mg protein vs. 3.03±0.11, p<0.001), TAS (1.02±0.01mmol/L vs. 1.19±0.02, p<0.001), and UA (298.0±6.68µmol/L vs. 383.0±6.55, p<0.001) was observed at high altitude. These measurements were significantly lower in highlanders than in lowlanders at high altitude. Total antioxidant status (TAS) and uric acid (UA) showed a positive correlation in lowlanders at sea level and in highlanders at high altitude. Hydroperoxide and TAS also showed a positive correlation in both groups at high altitude. This indicates increased oxidative stress at high altitude despite an increase in antioxidant capacity in lowlanders. To conclude, a hypoxia-induced increase in UA contributes an appreciable portion of plasma total antioxidant capacity, but may not be effective in preventing oxidative stress at high altitude.